Spare Part Warehouse Stock Inventory With Min-Max Method - Foezi Arisandi Foezi; Nila Natalia; Aziz Abdullah (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2024)
In the current technological era, data and inventory management have become very important, especially for spare part transaction data. CV. Razza Cipta Lestari, a company in the woodworking industry, faces issues with their manual inventory management system. This system tends to rely on intuition and experience to determine stock availability, which can result in unexpected stockouts or overstocking. To address this issue, the author suggests implementing the Min-Max method in spare part management. This method sets maximum and minimum inventory levels, aiming to reduce human error, prevent stockouts, and avoid overstocking. This research is specifically developed for CV. Razza Cipta Lestari, with the Min-Max method chosen for its effectiveness in maintaining smooth production. Based on trial results from two actual usage data of hydraulic oil and nails, the calculated stock levels ensure sufficient stock availability and prevent both stockouts and overstocking